Does Planter Pressure Distribution Alter with Weight Reduction in Obese Children? - Radwan, Nadia L.; Ibrahim, Marwa M. (Journal of Medical Biomedical and Applied Sciences, 2017)
Background: High plantar pressure values in obese children are of great concern due to the risk of inducing pain, discomfort, and foot pathologies, mainly for childrenâs growing feet. Obese children have been observed to have flat feet compared to those of their non-obese correspondents. Objective: The purpose of this study was to detect whether there were differences in the static and dynamic planter pressure distribution variables after weight reduction in obese children. Methods: Thirty obese prepubescent girls aged from 8 to 11 years were included in the study. The Tekscan foot pressure system was used to measure the static and dynamic plantar pressures before and after nine months of weight reduction program. The peak pressures beneath the forefoot, midfoot and rearfoot were measured for each foot. The weight reduction program consists of a combined dietary and exercise program. Results: The study revealed high significant differences in the peak force, contact area and in plantar pressure in standing. Significant differences were also found in dynamic pressure variables particularly under the mid foot region which was highly significant. Conclusion: It was concluded that decreasing the weight of obese children is an important issue because it will decrease both static and dynamic pressure variables, and in consequence decreasing the risk of obtaining foot problems, stress fractures, or ulcerations caused by effect of their increased weights  on their growing feet.